Corporate Social Responsibility and the Paradoxes of State Capitalism Ethnographies of Norwegian Energy and Extraction Businesses Abroad - Knudsen, Ståle (Dislocations, 2023)
Through a series of case studies in diverse regions of the world, this book explores how transnational Norwegian energy and extractive industries handle corporate social responsibility (CSR) when operating abroad in places such as China, Brazil, and Turkey. With significant state ownership and embeddedness in the Nordic societal model, Norwegian capitalism is often represented as "benign" or ethical. By tracing CSR policy and practice-from headquarters to operations-this volume critically explores the workings of Norwegian corporate capitalism and its engagement with key issues of responsibility, accountability, and sustainability.